Die Wende in der Wahrnehmung der Ostdeutschen. Eine Mentalitätsgeschichte. - Philipp Ebell (Historia.scribere)
The following paper examines the question of how eastern German people perceived the “turnaround“ in the 1980s and 90s. Therefore, six people who came from various social backgrounds were interviewed. In addition, the interviews were analyzed and compared to historical data in order to find out how and why people experienced the “turnaroun